The history of knowledge - Östling, Johan; Heidenblad, David Larsson, 1983- (Cambridge elements. Elements in historical theory and practice,, 2023)
This Element provides a pedagogical overview of the history of knowledge, including its main currents, distinguishing ideas, and key concepts. However, it is not primarily a state-of-the-art overview but rather an argumentative contribution that seeks to push the field in a certain direction - towards studying knowledge in society and knowledge in people's lives. Hence, the history of knowledge envisioned by the authors is not a rebranding of the history of science and intellectual history, but rather a reinvigoration of social and cultural history. This implies that many different forms of knowledge should be objects of study. By drawing on ongoing research from all across the world dealing with different time periods and problems, the authors demonstrate that the history of knowledge can enrich our understanding of past societies. This title is also available as Open Access on Cambridge Core.